Analisis Pengaruh Alokasi DAK Masing-Masing Bidang Terhadap Tingkat Kemiskinan di Kabupaten Pandeglang dan Kabupaten Lebak - Asti Yayuk Wahyuni; Bambang Juanda; Yeti Lis Purnamadewi (Department of Urban and Regional Planning, Diponegoro University, 2021)
Fiscal decentralization is one of the government’s strategies to improve people’s welfare. The fiscal decentralization policy instrument that can directly affect the quality of local government spending is The Specific Allocation Fund (DAK). The DAK management in the financial aspect has a few problems, nonoptimal regional government performance and mismatched allocation and government needs. Proposal based The Specific Allocation Fund (DAK) hopefully could adjust the development priorities determined by regional conditions, government needs, and undeveloped villages with high-level poverty. Pandeglang and Lebak Regency are the region with the highest poverty level in Banten Province. This study aims to analyze the DAK effect of each sector on poverty in Pandeglang and Lebak Regency. The analysis used Geographical Weighted Regression (GWR) with DAK data for each field in 2018 and poverty data in 2019. The result showed that DAK variables in education, health, and agriculture tended not to reduce poverty rates. The DAK variable in the housing and settlement sector, the marine and fisheries sector, the tourism sector, and the market sector tended to reduce poverty. At the same time, the DAK variable in Road, sanitation, and village funds tended to reduce poverty levels in most districts. Based on the study, the poverty alleviation program in each district is adjusted to each of the DAK sectors that are influential. However, the result indicated that the adjustment of DAK sectors influenced the poverty alleviation program in every district in Pandeglang and Lebak Regency.